Dynamics of Pepper Trade in West Coast of Aceh, 1873-1921 - Nurul Romdloni; Singgih Sulistiyono; Yety Rochwulaningsih (IHiS (Indonesian Historical Studies), 2019)
The West Coast of Aceh has been one of the largest pepper producing centers in Southeast Asia since the end of the 18th century. The war that began in the Netherlands in 1873 resulted in trade in the West Coast of Aceh being hampered. The beach blockade carried out by the Dutch made the distribution of pepper disrupted. The scorched earth tactics resulted in the decline of pepper production. The condition of pepper trade on the West Coast of Aceh, which had already deteriorated, was no longer able to rise, even after the Aceh War was over. The poor condition of pepper trade on the West Coast of Aceh was compounded by the increasing demand for other commodities such as copra, kapok, and patchouli oil. Private capital that began to be opened after the war flowed more to the development of various new commodities. The research found that the export of pepper commodities from the West Coast of Aceh was far behind the East Coast of Aceh.